Criteria for Critical Care Infants and Children: PICU Admission, Discharge, and Triage Practice Statement and Levels of Care Guidance. Issue 9 (September 2019) - Frankel, Lorry R.; Hsu, Benson S.; Yeh, Timothy S.; Simone, Shari; Agus, Michael S. D.; Arca, Marjorie J.; Coss-Bu, Jorge A.; Fallat, Mary E.; Foland, Jason; Gadepalli, Samir; Gayle, Michael O.; Harmon, Lori A.; et al.
Abstract : Objectives: To update the American Academy of Pediatrics and Society of Critical Care Medicine's 2004 Guidelines and levels of care for PICU. Design: A task force was appointed by the American College of Critical Care Medicine to follow a standardized and systematic review of the literature using an evidence-based approach. The 2004 Admission, Discharge and Triage Guidelines served as the starting point, and searches in Medline (Ovid), Embase (Ovid), and PubMed resulted in 329 articles published from 2004 to 2016. Only 21 pediatric studies evaluating outcomes related to pediatric level of care, specialized PICU, patient volume, or personnel. Of these, 13 studies were large retrospective registry data analyses, six small single-center studies, and two multicenter survey analyses. Limited high-quality evidence was found, and therefore, a modified Delphi process was used. Liaisons from the American Academy of Pediatrics were included in the panel representing critical care, surgical, and hospital medicine expertise for the development of this practice guidance. The title was amended to "practice statement" and "guidance" because Grading of Recommendations, Assessment, Development, and Evaluation methodology was not possible in this administrative work and to align with requirements put forth by the American Academy of Pediatrics. Methods: The panel consisted of two groups: a voting group and a writing group. The panel used an iterative collaborative approach to formulate statements on the basis of the literature review and common practice of the pediatric critical care bedside experts and administrators on the task force. Statements were then formulated and presented via an online anonymous voting tool to a voting group using a three-cycle interactive forecasting Delphi method. With each cycle of voting, statements were refined on the basis of votes received and on comments. Voting was conducted between the months of January 2017 and March 2017. The consensus was deemed achieved once 80% or higher scores from the voting group were recorded on any given statement or where there was consensus upon review of comments provided by voters. The Voting Panel was required to vote in all three forecasting events for the final evaluation of the data and inclusion in this work. The writing panel developed admission recommendations by level of care on the basis of voting results. Results: The panel voted on 30 statements, five of which were multicomponent statements addressing characteristics specific to PICU level of care including team structure, technology, education and training, academic pursuits, and indications for transfer to tertiary or quaternary PICU. Of the remaining 25 statements, 17 reached consensus cutoff score. Following a review of the Delphi results and consensus, the recommendations were written. Conclusions: This practice statement and level of care guidance manuscript addresses important specifications for each PICU level of care, including the team structure and resources, technology and equipment, education and training, quality metrics, admission and discharge criteria, and indications for transfer to a higher level of care. The sparse high-quality evidence led the panel to use a modified Delphi process to seek expert opinion to develop consensus-based recommendations where gaps in the evidence exist. Despite this limitation, the members of the Task Force believe that these recommendations will provide guidance to practitioners in making informed decisions regarding pediatric admission or transfer to the appropriate level of care to achieve best outcomes. Abstract : Supplemental Digital Content is available in the text.